1993
DOI: 10.1210/endo.132.1.7678217
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure to melatonin leads to time-dependent sensitization of adenylate cyclase and down-regulates melatonin receptors in pars tuberalis cells from ovine pituitary.

Abstract: In photoperiodic mammals, seasonal cycles of growth and reproduction are cued by changes in the duration of the nocturnal profile of secretion of the pineal hormone melatonin. To investigate the likely mode of action of this hormone on target tissues, the effect of prolonged treatment with melatonin on the sensitivity of the adenylate cyclase (AC) system was examined in primary cultures of ovine pars tuberalis (PT) cells. When cells were exposed to melatonin (100 pM or 1 microM) for 16 h, and the hormone was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 22 publications
2
58
0
1
Order By: Relevance
“…The present study shows that subchronic (4 days) melatonin treatment sensitizes the cAMP transduction system in the rat frontoparietal cortex, as revealed by subsequent increases in basal and FK‐stimulated AC activities. These results are in agreement with the studies in vitro in which prolonged exposure to melatonin leads to tissue‐dependent sensitization of AC in pars tuberalis cells from ovine pituitary [43]. Sensitization of AC after prolonged exposure to inhibitory agonists is a well‐established phenomenon [44, 45].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study shows that subchronic (4 days) melatonin treatment sensitizes the cAMP transduction system in the rat frontoparietal cortex, as revealed by subsequent increases in basal and FK‐stimulated AC activities. These results are in agreement with the studies in vitro in which prolonged exposure to melatonin leads to tissue‐dependent sensitization of AC in pars tuberalis cells from ovine pituitary [43]. Sensitization of AC after prolonged exposure to inhibitory agonists is a well‐established phenomenon [44, 45].…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in agreement with studies from Hadley [41] who demonstrated that continuous exposure to melatonin renders the target tissue unresponsive to the hormone. Previously, it had been reported that the total number of melatonin receptors in the hippocampus midbrain [42], and pars tuberalis of the anterior pituitary [43] may be reduced following prolonged exposure to melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…The expressed receptor coupled to a Gi protein in the host cells suggesting that the cAMP signal transduction pathway is possibly the major effector for the anti‐proliferative effects of melatonin. Although it is well known that melatonin is able to cause auto‐ [42] and hetero‐ [43] desensitizing effects on biological responses, it is interesting to mention that melatonin did not cause auto desensitization of S‐91 cells expressing the MT‐1 receptor, even after prolonged exposures for 96 hr or at high concentrations used in our experiments.…”
Section: Discussionmentioning
confidence: 75%
“…However, the overall amplitude of the pCREB rhythm in MT1/2-false/- mice is significantly dampened as compared to WT animals. It is well known that melatonin acutely inhibits cAMP accumulation and CREB phosphorylation . As an additional effect, chronic melatonin exposure (>4 hours) leads to a time‐dependent sensitization of the adenylyl cyclase in pars tuberalis cells .…”
Section: Discussionmentioning
confidence: 99%